2014
DOI: 10.1002/star.201400174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental factors on rice starch structure: A review

Abstract: Among cereal grains, rice is the world's leading source of caloric energy in the human diet. About 90% of a milled rice kernel is starch (dry weight basis), thus justifying the need to understand the impacts of factors affecting starch composition and behavior when processed. This review presents past and current perspectives regarding the effects of growing environment on the macro, micro, and nano level structures of rice starch. The environmental elements considered in this work are: air temperature, atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 113 publications
(185 reference statements)
4
85
1
5
Order By: Relevance
“…Wild type Angular, polygonal (Hoover et al, 1996) < 20 (Singh et al, 2003) 2-8 (Hoover et al, 1996;Patindol et al, 2015) 0.6-1.4 (Dhital et al, 2011) 0.1 (Hoover et al, 1996) 0.1 (Lim et al, 1994) 21-25 (Patindol et al, 2015) Waxy 0-2 (Patindol et al, 2015) High amylose > 25 (Patindol et al, 2015) Corn Wild type Angular (Singh et al, 2003) 11.5± 0.3 (López et al, 2010) 0.6-0.8 (Dhital et al, 2011) 0.3-0.53 (Morrison et al, 1984) 0.4 (Dhital et al, 2011) 0.31-0.35 (Sang et al, 2007) 28. 5 Nuwamanya et al, 2013) 23.86 ± 0.66 (López et al, 2010) 25.8-32.5 (Morrison et al, 1984) 19.2 ±1.4/A (López et al, 2010) Waxy 0.01-0.05 (Morrison et al, 1984) 1.4-2.7 (Morrison et al, 1984) High amylose Polygonal and Angular (Ellis et al, 1998) 0.38-0.67 (Morrison et al, 1984) 0.02 (Lim et al, 1994) 70 (Lim et al, 1994) 42.6-67.8 (Morrison et al, 1984) Lipid, protein and phosphorus contents are shown as % of total dry weight.…”
Section: Ricementioning
confidence: 99%
“…Wild type Angular, polygonal (Hoover et al, 1996) < 20 (Singh et al, 2003) 2-8 (Hoover et al, 1996;Patindol et al, 2015) 0.6-1.4 (Dhital et al, 2011) 0.1 (Hoover et al, 1996) 0.1 (Lim et al, 1994) 21-25 (Patindol et al, 2015) Waxy 0-2 (Patindol et al, 2015) High amylose > 25 (Patindol et al, 2015) Corn Wild type Angular (Singh et al, 2003) 11.5± 0.3 (López et al, 2010) 0.6-0.8 (Dhital et al, 2011) 0.3-0.53 (Morrison et al, 1984) 0.4 (Dhital et al, 2011) 0.31-0.35 (Sang et al, 2007) 28. 5 Nuwamanya et al, 2013) 23.86 ± 0.66 (López et al, 2010) 25.8-32.5 (Morrison et al, 1984) 19.2 ±1.4/A (López et al, 2010) Waxy 0.01-0.05 (Morrison et al, 1984) 1.4-2.7 (Morrison et al, 1984) High amylose Polygonal and Angular (Ellis et al, 1998) 0.38-0.67 (Morrison et al, 1984) 0.02 (Lim et al, 1994) 70 (Lim et al, 1994) 42.6-67.8 (Morrison et al, 1984) Lipid, protein and phosphorus contents are shown as % of total dry weight.…”
Section: Ricementioning
confidence: 99%
“…A quadratic curve relationship exists between the amylose content and the temperature during the grain‐filling stage in most varieties and the temperature during the early grain‐filling period has the largest impact (Ahmed et al., ; Zhou, Zhang, Gao, & Zhu, ). Likewise, the amylose content of Indica cultivars was parabolically correlated to the temperature for 20 d after full heading under artificial temperature control (Patindol, Siebenmorgen, & Wang, ), although the amylose content was found to be negatively correlated with sunshine hours during the grain‐filling period (Yun et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental conditions such as the temperature and day length and genotype × environment interaction also affect the amylose content of different varieties of rice (Lin et al, 2005). Several other studies have shown that the interaction between genotype and ambient temperature also has an effect on amylose content in rice grains (Nkori Kibanda and Luzi-kihupi, 2007;Patindol et al, 2015). Thus, amylose content varies over seasons in the same site of cultivation even with the same variety (Inatsu, 1979;Asaoka et al, 1984).…”
Section: Introductionmentioning
confidence: 99%